Factors Affecting the Interest of Women of Reproductive Age Regarding Visual Inspection of Acetic Acid during the Pandemic of Covid-19 - Realita, Friska; Kusumaningsih, Meilia Rahmawati; Muslimasari, Wiwi (JURNAL KEBIDANAN, 2024)
One of the biggest causes of death for women in Indonesia is cervical cancer. The incidence of cervical cancer in Indonesia was 0.8% or 23.4/100,000 population. Delay in early detection is the main cause of the high incidence of cervical cancer in Indonesia. Patients with cervical cancer are generally detected at an advanced stage. This is caused by the awareness of WRA to carry out early detection of cervical cancer through IVA examination which is still very low. To find out the factors that influence interest of of women of reproductive age (WRA) in the Acetic Acid Visual Inspection (IVA) examination during the Covid-19 pandemic in the working area of the Kebun Tebu Health Center, West Lampung Regency. This was a cross sectional study. The population in this study was 459 women who were taken from the target number of IVA examinations at the working area of Health Center of Kebun Tebu  in 2022. The number of samples in this study were 78 respondents. Measuring tool used in this study was a questionnaire. This research was conducted from October - November 2022 at the Kebun Tebu Health Center, West Lampung Regency, Indonesia until the sample and research data limits were met. The results of this study showed that the education level did not influence interest with a p-value of 0.423, knowledge level influenced WRA interest with a p-value of 0.024, attitude level influenced WRA interest with a p-value of 0.037, husband's level of support did not affect WRA interest with a p-value of 0.313 , and the level of information access influences WRA interest with a p-value of 0.030. Knowledge factors, attitude factors, and information access factors influenced WRA interest in conducting an Acetic Acid Visual Inspection (IVA) examination. Meanwhile, the Education Factor and the husband's support factor did not affect WRA interest in conducting an IVA during the Covid-19 pandemic in the working area of the Kebun Tebu Health Center.